SIMULASI MODEL FISIK EFEKTIVITAS PEMECAH GELOMBANG TETRAPOD DAN DOLOS - Maratus Khasanah Humairah; Sugeng Widada; Rikha Widiaratih (JURNAL TEKNIK HIDRAULIK, 2022)
In order to create  calm ocean water, breakwater is essential for reducing wave energy. Rubble-mound breakwater with tetrapod and dolosse armor can be a solution in reducing ocean wave energy. This research aims to understand the effectiveness of rubble-mound tetrapod and dolosse breakwater in reducing wave energy with sea level condition variation in a laboratory. The method of this research is an experimental method that uses a breakwater physical model with various scenarios. Testing scenarios are determined based on water depth, wave period (T), and armour structure. The results of this research showed that rubble-mound tetrapod breakwater is the most effective breakwater with an average reducing percentage of 86.7%. Rubble- mound tetrapod and dolosse breakwater physical model have high effectiveness because they are built by rubble mound structure that forms a sloping side. These structures are effective in reducing wave energy because the waves get in between rock slits. So, the wave energy reduces when it passes through the breakwater. This research can give some information and analysis in planning a breakwater effectively and efficiently in the ocean.Keywords: breakwater physical model, tetrapod, dolosse, wave energy